Social Interaction on Platform X (Case Study: Komunitas Murah-Murah) - Khansa Syarifah Alya Aziz; Tyas Nur Aini; Aghnia Dian Lestari (Athena: Journal of Social, Culture and Society, 2025)
Technological advances create new innovations for social media, such as X which provides community features that can be utilized by its users, one of which is the Komunitas Murah-Murah. This research aims to find out how social interactions and communication processes are carried out in the Komunitas Murah-Murah and the impact felt by its members. The research method used is qualitative with a case study approach and conducts observation, interviews and documentation as data collection techniques. The data validity test was carried out using the source triangulation method. This research uses symbolic interaction theory which includes five basic concepts: self, action, object, interaction, and collective action to analyze the dynamics of communication in the community. The results of this study show that social interactions carried out using symbols in the form of images and clear language can determine the decision-making process. Community members feel positive impacts such as ease of interaction, time flexibility, and wider information dissemination. The researcher identified negative impacts that hindered the interaction process, namely user dissatisfaction and fraud cases. The communication process applied in the Komunitas Murah-Murah is interactional, where members provide feedback to each other to create interaction and transactions. This research can contribute to the literature related to social interaction on social media.